Let Q n denote the quadratic mean of ( 0 n ) , ( 1 n ) , ( 2 n ) , … , ( n n ) .
Find n → ∞ lim n Q n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Wow! I did the same thing.... well without knowing a thing about Vandermonde's identity(means I didnt knew it by name) or Stirling's Formula. Nice question!
By the definition of the quadratic mean we n Q m = ( n 1 r = 0 ∑ n ( ( r n ) ) 2 ) 2 n 1 = ( n 4 n ) 2 n 1 = 2 n n 2 Thus the limit is 2 n → ∞ lim n − 2 n 1 = 2 n → ∞ lim exp ( − 2 n lo g n ) = 2 e − 0 = 2
Here is the proof for the first part
I’m sorry if I sound silly but in the first equation, quadratic mean is the “sum of squares”, not the “square of sum”.🤨
Problem Loading...
Note Loading...
Set Loading...
We note that Q n is defined as follows:
Q n = n ∑ k = 1 n ( k n ) 2 = n ( n 2 n ) By Vandermonde’s identity: ( k m + n ) = r = 0 ∑ n ( r m ) ( k − r n ) putting m = k = n .
Then, we have:
n → ∞ lim n Q n = n → ∞ lim 2 n n ( n 2 n ) = n → ∞ lim ( n ( n ! ) 2 ( 2 n ) ! ) 2 n 1 = n → ∞ lim ( n ( 2 π n ) ( e n ) 2 n 4 π n ( e 2 n ) 2 n ) 2 n 1 = n → ∞ lim ( n π n 2 2 n ) 2 n 1 = n → ∞ lim π 4 n 1 n 4 n 3 2 = 2 By Stirling’s formula: n ! ∼ 2 π n ( e n ) n Note that n → ∞ lim π 4 n 1 = 1 and n → ∞ lim n 4 n 3 = 1 (see note).
Note:
n → ∞ lim n 4 n 3 = n → ∞ lim exp ( 4 n 3 ln ( n ) ) = exp ( n → ∞ lim 4 n 3 ln ( n ) ) = exp ( n → ∞ lim 4 n 3 ) = e 0 = 1 where exp ( x ) = e x A ∞ / ∞ case, L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t. n .
References: